Project-Based Learning and the Impact it can Make in Social Studies Content (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2022)
The purpose of this manuscript is to explore the benefits of project-based learning (PBL), specifically regarding the content area of social studies. It is important for teachers to understand the benefits of incorporating this method. When students are active in the learning process, they are more engaged and curious. Incorporating project-based learning into the classroom can help make the experience more memorable and in result, help the students achieve the learning objectives. This manuscript will address the benefits of this method and provide real-world examples to use within a classroom.
Keywords: Lessons; Project-based learning; Social Studies; motivation